Bidirectional coupling method for solving the electromagnetic-joule thermal properties of electromagnetic launcher. Issue 1 (1st November 2022) - Zhang, Pengxiang; Shu, Tao
Abstract: The actual working process of the electromagnetic launcher is very complex, and using simulation software to solve it is the main method of research at this stage. The one-way coupling method will ignore the temperature-dependent characteristics of the material. In order to better simulate the actual working process, this paper uses the bidirectional coupling simulation method to solve the electromagnetic force and Joule heat of the four-rail electromagnetic launcher, and compares it with the unidirectional coupling. The simulation results show that the bidirectional coupling is more accurate than the unidirectional coupling, and the increase of the number of iterations will improve the solution accuracy, but affect the solution speed.